Hubungan Body Image dengan Diet Remaja Putri SMA Negeri 1 Kulisusu Utara Kabupaten Buton Utara - Ihsan, Habib; Nilasari, Nilasari (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2017)
Diet is one of the efforts made to lose a person's weight. Many teenagers are dissatisfied with their appearance, especially regarding body image or perception of their body which includes body shape and size. This study aims to determine the relationship between body image and the diet of young women in SMA Negeri 1 Kulisusu Utara, North Buton Regency. This research is a descriptive analytic study with a cross sectional study design and has been carried out on 17-22 July. The population was all students of class X and XI of SMA Negeri 1 Kulisusu Utara, North Buton Regency as many as 180 people and a sample of 124 people obtained using the proportional stratified random sampling technique. Data were collected using a questionnaire and analyzed using the chi-square test. The results showed that from 124 samples, most of them were 55 people (44.4%) with negative body image, unhealthy diet and 30 people (24.2%) with positive body image, healthy diet, then 21 people (16.9). %) with positive body image, unhealthy diet and 18 people (14.5%) with negative body image, had a healthy diet. The results of the chi-square test obtained p value of 0.001. The conclusion in this study is that there is a relationship between body image and the diet of young women in SMA Negeri 1 Kulisusu Utara, Buton Regency. Suggestions in this study are for SMA Negeri 1 Kulisusu to provide counseling or socialization about nutritional status and a healthy diet, especially for young women. For young women to apply healthy dietary behavior and understand the condition of their nutritional status, which in general have normal nutritional status, so there is no need to do the wrong diet. For further researchers, in order to be able to examine other factors that cause the wrong diet in young women of SMA Negeri 1 Kulisusu.